Grain yield correction methods related to adaptability and stability of corn cultivars - Filho, Alberto Cargnelutti; Storck, Lindolfo (Pesquisa Agropecuaria Brasileira, 2004)
The objective of this research was to verify if grain yield corrections could interfere in adaptability and stability parameters of corn cultivars. Yield corrections of 31 corn competition trials were done, based on plant populations. Actual data was compared with corrected data based on plant average yield, Zuber method, mean population covariance, recommended population covariance, Cruz method, Vencovsky & Cruz method and stratified correction method. The magnitude of correction interferences was verified using the statistics of square mean deviations of each adaptability and stability parameters and concordance index. Corrections based upon mean and recommended population covariance, Vencovsky & Cruz methods and stratified method have the lowest discordance compared to adaptability and stability parameters of corn cultivars of actual grain yield data.
Keywords: Zea mays; covariance; uniformity; statistics analysis; experimental precision